2023
DOI: 10.5194/amt-16-2455-2023
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of the Alphasense OPC-N3 and Plantower PMS5003 sensor in measuring dust events in the Salt Lake Valley, Utah

Abstract: Abstract. As the changing climate expands the extent of arid and semi-arid lands, the number of, severity of, and health effects associated with dust events are likely to increase. However, regulatory measurements capable of capturing dust (PM10, particulate matter smaller than 10 µm in diameter) are sparse, sparser than measurements of PM2.5 (PM smaller than 2.5 µm in diameter). Although low-cost sensors could supplement regulatory monitors, as numerous studies have shown for PM2.5 concentrations, most of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…A relatively poor fit was achieved for the PM 10 concentrations (R 2 = 0.66). This low coefficient can be explained by the overestimation of the PM 10 concentrations by OPC-N3 and its predecessor model, OPC-N2 [69].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…A relatively poor fit was achieved for the PM 10 concentrations (R 2 = 0.66). This low coefficient can be explained by the overestimation of the PM 10 concentrations by OPC-N3 and its predecessor model, OPC-N2 [69].…”
Section: Resultsmentioning
confidence: 98%
“…A relatively poor fit was achieved for the PM10 concentration (R 2 = 0.66). This low coefficient can be explained by the overestimation of the PM10 co centrations by OPC-N3 and its predecessor model, OPC-N2 [69]. For particulate matter, PM 2.5 showed a high fit (R 2 = 0.85) between the Nova SDS011 sensor (Nova Fitness, Jinan, China) used for HZS-GARP-AQ-04 and the Alphasense OPC-N3 in the Libelium system.…”
Section: Resultsmentioning
confidence: 98%
“…In recent years, commercially available, low‐cost air quality sensors have become common, and regulatory agencies started using them to obtain more granular information on air quality spatial and temporal distribution (Jaffe et al., 2023). However, the accuracy and precision of these sensors need to be characterized (Zheng et al., 2018), the sensors require calibrations (Ardon‐Dryer et al., 2020) and recent work suggests they are unable to accurately characterize coarse particles (>2.5 μm) (Jaffe et al., 2023; Kaur & Kelly, 2023; Rueda et al., 2023) and they still contain spatial gaps. These spatial gaps limit our ability to fully quantify the number and nature of dust events and their subsequent impacts.…”
Section: Large Spatial Gaps In Data Results In Unmonitored Eventsmentioning
confidence: 99%
“…As stated in [16], previous studies report that Alphasense OPCs demonstrate strong correlations (R2 = 0.93-0.99) with PM10 in controlled laboratory investigations [17][18][19][20]. However, field-based studies have indicated relatively lower correlations (R2: 0.53-0.8) [21][22][23], primarily due to the variability in ambient meteorological conditions and fluctuations in PM compositions.…”
Section: Opc-n3mentioning
confidence: 93%